Evaluation the Effect of Treatment on Melatonin Levels among Male with Nephrolithiasis - Omar Khalid Suhail (Journal of Global Pharma Technology, 2018)
Kidney stone formation is the source of the common disease nephrolithiasis. Oxidative stress has been increasingly linked to the high incidence of this disease. The hormone melatonin (MLT) is a biogenic amine, plays a role in the human body as an antioxidant and anti-inflammatory parameter; also it could be effective in preventing cell damage. In this study fifty-five male with nephrolithiasis with age and gender-matched (30) apparently, healthy individuals were involved. Twenty0-two of the patients treated with Tamsulosin hydrochloride and potassium citrate treatments were also comprised. Determination of sera and urine contents of urea, creatinine, electrolytes, and MLT levels were carried out. The urea and creatinine concentrations reveal significant increases in sera of patients in comparison to that of control.  A decrease in serum MLT concentration was observed in patients groups in comparison to those of control, while a highly significant diminution in urine MLT concentration was indicated in patients groups after treatment in comparison with that of other groups. As a conclusion the MLT  concentrations were altered in nephrolithiasis patients in comparison with its concentrations in both patients after treatment and healthy subjects, that proved the important role of  MLT as an antioxidant and anti-inflammatory parameter in nephrolithiasis; as well increasing MLT dietary intake or on supplementation was recommend. Keywords: Treatment, Melatonin Levels, Nephrolithiasis.